2023
DOI: 10.22541/au.167813546.63449155/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the advanced microstructural characterisation of additively manufactured alumina-zirconia based eutectic ceramics: Overview and outlook

Abstract: Recently, there have been a number of reports on the fabrication of Alumina-Zirconia (Al2O3-ZrO2 (AZ))-based eutectic ceramics using laser additive manufacturing (AM) techniques owing to the exceptional creep and oxidation resistance coupled with excellent microstructural stability in these materials. Moreover, a number of interesting microstructural features (in these materials) have been reported to be formed by the variation of process parameters (especially, laser scanning speed) associated with the aforem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Moreover, as mentioned in section 1, laser AM-based techniques are based on layer-by-layer deposition of materials. This adds up to the complexity (in terms of obtaining GBE microstructures) by inducing large-scale microstructural heterogeneities (with high defect concentration) [32][33][34][35][36][37][38][39][40][41], resulting in non-equilibrium microstructures. Hence, obtaining GBE microstructures in AM-based AZ ceramics provides an immense potential towards future investigations in field of AZ ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as mentioned in section 1, laser AM-based techniques are based on layer-by-layer deposition of materials. This adds up to the complexity (in terms of obtaining GBE microstructures) by inducing large-scale microstructural heterogeneities (with high defect concentration) [32][33][34][35][36][37][38][39][40][41], resulting in non-equilibrium microstructures. Hence, obtaining GBE microstructures in AM-based AZ ceramics provides an immense potential towards future investigations in field of AZ ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of correlative microscopy [1] has completely revolutionised the field of research in structural materials. Ranging from the study of segregated atoms [4,5,10] to characterising nanoscale precipitates at different interfaces [5], the novel technique has enabled material scientists to correlate the properties of a material with its bulk and interfacial structure, simultaneously. From the fundamental viewpoint, there still remain a lot of unexplored avenues, in the context of oxidation studies in the UHTCMCs, which may be potentially addressed by this novel technique.…”
Section: A Few Presently Unexplored Avenues In This Field and Outlook...mentioning
confidence: 99%
“…Unfortunately, at present, there is limited understanding of the effect of volume expansion associated with the formation of MoO3 at temperatures lower than 1200 ˚C on the stress pile-up at GBs. Hence, its the GB cohesion [10] and GB energy [5] which needs to be addressed, for a detailed understanding of the influence of the same on the stress pile-up associated with volume expansion, due to formation of MoO3, in the present context. Besides, adhesion between the oxide layer and the surface of the base material (ZrB2-MoSi2, in the present context) is also something which needs to be addressed as a function of the local chemistry at the substrate-oxide interface before subjecting these materials to service at elevated temperatures.…”
Section: A Few Presently Unexplored Avenues In This Field and Outlook...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the current studies reported have been mainly restricted to thin-walled or long, cylinder-shaped, alumina-zirconia-based eutectic ceramics: for example, Al 2 O 3 -GdAlO 3 -ZrO 2 [27,82,83,92,93], Al 2 O 3 -ZrO 2 [77,80,91], Al 2 O 3 -GdAlO 3 [25], Al 2 O 3 -YAG-ZrO 2 [78], Al 2 O 3 -YAG [31], etc. Detailed descriptions of the microstructures and crystallography of alumina-zirconia-based nanoeutectic ceramics fabricated with laser AM can be found in the recently published literature [94].…”
Section: Laser Additive Manufacturingmentioning
confidence: 99%